Work-conflict, job satisfaction and self-efficacy on organisational commitment of workers in selected banks in Lagos State (2020)
Organizational Commitment is the psychological attachment that employees have with their organizations. This plays a big role in ascertaining the bond that employees share with the organization, which helps to enhance employees' value to it. This study, therefore, investigated the influence of work conflict, job satisfaction and self-efficacy on organizational commitment of bankers in Lagos. The study adopted descriptive design using simple random sampling in thè selection of three hundred bankers. Work conflict, job satisfaction, organisational commitment and self efficacy scales were used. Data were analysed using Pearson product moment correlation at 0.05 level of significant. The independent variables significantly correlated thè dependent variable - organizational commitment of bankers in Lagos, (r = 0.67). This implies that work conflict is significant correlated to organizational commitment among bankers. Each of the independent variables made relative contribution as in thè following order self-efficacy and organizational commitment (r 0.47). Significant association was observed between job satisfaction and organizational commitment among bankers; (r = 0.64). The study recommended that these variables be taken into consideration as a means of enhancing the organisational commitment of bankers in an organisation. Also bank management, government and stakeholders can put in place intervention and motivation as a process towards promoting organizational commitment.